2018
DOI: 10.1038/s41598-018-24414-y
|View full text |Cite|
|
Sign up to set email alerts
|

Anisomycin prevents OGD-induced necroptosis by regulating the E3 ligase CHIP

Abstract: Necroptosis is an essential pathophysiological process in cerebral ischemia-related diseases. Therefore, targeting necroptosis may prevent cell death and provide a much-needed therapy. Ansiomycin is an inhibitor of protein synthesis which can also activate c-Jun N-terminal kinases. The present study demonstrated that anisomycin attenuated necroptosis by upregulating CHIP (carboxyl terminus of Hsc70-interacting protein) leading to the reduced levels of receptor-interacting protein kinase 1 (RIPK1) and receptor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 45 publications
1
22
1
Order By: Relevance
“…In our study, CHIP protected N2a cells following oxygen glucose deprivation (OGD) through inhibiting necroptosis 30 . In detail, we detected upregulation of RIPK1, RIPK3, and MLKL in N2a cells exposed to OGD accompanied by increased cell death, and Nec-1, a RIPK1 inhibitor, could reverse these effects 30 . These results suggested that necroptosis was activated under OGD challenging.…”
Section: Ischemic Strokementioning
confidence: 66%
See 4 more Smart Citations
“…In our study, CHIP protected N2a cells following oxygen glucose deprivation (OGD) through inhibiting necroptosis 30 . In detail, we detected upregulation of RIPK1, RIPK3, and MLKL in N2a cells exposed to OGD accompanied by increased cell death, and Nec-1, a RIPK1 inhibitor, could reverse these effects 30 . These results suggested that necroptosis was activated under OGD challenging.…”
Section: Ischemic Strokementioning
confidence: 66%
“…Moreover, while other functions of anisomycin may contribute to the benefit of OGD, the role of CHIP may be much more important 30 . Neither the TPR nor the U-box domain of CHIP alone possesses the protective function of inhibiting necroptosis, suggesting that both the co-chaperone and ubiquitin E3 ligase functions of CHIP are necessary for anti-necroptosis following OGD 30 . Similarly, Cabral-Miranda et al reported that CHIP overexpression protected against hippocampal neuronal death through decreasing the phosphorylation of eIF2a and AKT in experimental brain ischemia 34 .…”
Section: Ischemic Strokementioning
confidence: 99%
See 3 more Smart Citations